Obstacles of applying electronic administration in school administration from the point of view of Jordanian school principals - Al-Azeh, Mohammed Jamal Mohammed (Journal of Educational and Psychological Sciences, 2022)
The study aimed at identifying the obstacles of implementations electronic administration in school administration from the point of view of the Jordanian school principals. To achieve this goal, the descriptive-analytical approach with its qualitative content was used, as interviews were conducted with 20 principals in the schools of the North Eastern Badia District of the Directorate of Education in Jordan.The study concluded that among the most important obstacles to the application of electronic administration in school administration is (1) the difficulty of solving technical problems faced by the school administration, (2) the lack of sufficient awareness among teachers of electronic culture and the importance of electronic administration applications in school administration, (3) the lack of classrooms containing the necessary electronic devices, (4) the lack of Funding and infrastructure that result in the inability to provide computer accessories, (5) and the lack of trained human cadres to apply electronic management in school administration. In light of the results that have been reached, it was recommended to emphasize the need to emphasize the training of principals in particular, and teachers in general, on the use of electronic management in administrative school work, and to prepare a guide for the concept of electronic management, its objectives, and its fields in school work, as this contributes to spreading a greater culture of management.
Keywords: school administration; electronic administration; Jordanian school principals; internet; computer